Data Science: The Development of an Age of Innovation and Opportunity (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Today's period digital technologies each per second developing in time big in volume data work release business It's difficult and even more so big opportunities open will give. This from the data necessary has been thoughts get different in the fields to success to reach important source is counted. This on the ground basically dynamic and interdisciplinary field Data science is important important has​ This In the article we enter the world of data science come in we will go and his information in the field of technologies (IT). importance we learn